IMPLEMENTASI MANAJEMEN PENDIDIKAN KARAKTER DALAM MENGEMBANGKAN MINAT SIKAP DAN PERILAKU POSITIF SISWA - INDRA KURNIAWAN; Achmad Asrori; Untung Sunaryo (UNISAN JURNAL, 2022)
Character education requires strong collaboration with the education curriculum in schools, especially Madrasah Level Education where the education management that is implemented must be able to support the education of children's positive attitudes and behaviors. Therefore, this study aims to describe and understand education management in madrasah education units and the implementation of education management in improving the education of students' interests, attitudes and behavior. Methods This research uses a qualitative approach with triangulation data collection techniques. The location of the research is the Nurul iman margotani Education Foundation in the Madrasah Ibtidaiyah Al-Fatah Sindang Anom Institute. The results showed that the implementation of character education management in developing students' interests, attitudes and behavior was based on objective planning with clear and specific goals, having regular education programs, developing activities in the form of intra-curricular, extracurricular, guidance and counseling of activity programs with the goal is to build character education for students, increase student skills in the practice of humanizing humans and other skills.Keywords : Character Education Management, Interest Attitudes and Positive Behavior